Haematological parameters and production characteristics of novel Romanov × Hissar crossbred sheep adapted to European steppe climate - Pokhil, Volodymyr; Pokhil, V.; Pokhil, V. I.; Pokhyl, V.; Pokhyl, V. I.; Pohyl, V.; Pohyl, V. I.; Pohil, V.; Pohil, V. I.; Pokhyl, Volodymyr Ivanovych; Pokhil, Vladimir; Pohil, Vladimir; et al. (Croatian Veterinary Institute, Zagreb, 2023)
The study presented some haematological parameters and production characteristics of novel crossbred Romanov × Hissar and purebred Romanov sheep. A number of biochemical and haematological tests were performed to assess the level of adaptation of F1 crossbred progeny to local rearing conditions and evaluate its potential economic benefits for industrial production. The newly created crossbreed demonstrated significant increase in carcass production characteristics, with pre-slaughter weight increased by 29.2%, slaughter weight - by 39.7%, cooled carcass weight - by 40.5% and total yield ‒ by 8.2% compared to Romanov purebreed. The meat quality was also increased: fat content remained at the same level (6.6-6.8%), carcasses of F1 crossbreed lambs had higher relative weight of muscle tissue (78.8% vs. 73.3%), increased content of the 1st grade meat (94.6% vs. 91.6%), and higher caloric value of the meat (by 8.7%) compared to the parent purebreeds. An increased erythrocyte (by 3.1%) and leukocyte (by 6.45%) count was noted in the F1 rams. Haemoglobin level in F1 lambs was increased by 4.2%. Protein metabolism parameters were improved: blood serum total protein level ‒ by 11.2%, albumin ‒ by 11.4%, globulin ‒ by 10.4%, suggesting intensified protein metabolism in F1 lambs; this was also evidenced by the increased activities of aspartate transaminase (by 3.9%) and alanine transaminase (by 16.6%) in F1 lambs over Romanov purebred animals. Blood serum of crossbred lambs had higher bactericidal (by 1.92%), lysozyme (by 3.53%), and phagocytic activity. The increased haematological and biochemical parameters and enhanced antibacterial properties of serum indicate the enhanced metabolic activity in F1 crossbreed sheep and underlay the improved meat production parameters. Obtained results demonstrate increased adaptation of the novel crossbred to industrial rearing conditions and local microclimate of steppe zone of Ukraine, which is undergoing gradual aridization. У дослідженні були представлені деякі гематологічні параметри та виробничі характеристики нового схрещування Романов × Гіссар та чистокровних Романовських овець. Було проведено низку біохімічних та гематологічних досліджень, щоб оцінити рівень адаптації потомства кросу F1 до місцевих умов вирощування та оцінити його потенційну економічну вигоду для промислового виробництва. Новостворений поміс продемонстрував суттєве підвищення забійних показників: передзабійна маса зросла на 29,2%, забійна – на 39,7%, маса охолодженої туші – на 40,5% і загальний вихід – на 8,2% порівняно з романівською чистою породою. Підвищилась і якість м’яса: вміст жиру залишився на колишньому рівні (6,6-6,8 %), у тушах ягнят помісі F1 зросла питома вага м’язової тканини (78,8 % проти 73,3 %), збільшився вміст м’яса 1-го сорту ( 94,6 % проти 91,6 %), а також вищу калорійність м’яса (на 8,7 %) порівняно з чистопорідними вихідними. У баранів F1 відзначено підвищення кількості еритроцитів (на 3,1%) і лейкоцитів (на 6,45%). Рівень гемоглобіну у ягнят F1 був підвищений на 4,2%. Поліпшилися показники білкового обміну: рівень загального білка сироватки крові – на 11,2%, альбуміну – на 11,4%, глобуліну – на 10,4%, що свідчить про інтенсифікацію білкового обміну у ягнят F1; про це також свідчить підвищення активності аспартаттрансамінази (на 3,9 %) і аланінтрансамінази (на 16,6 %) у ягнят F1 порівняно з чистопородними породами Романов. Сироватка крові ягнят помісей мала вищу бактерицидну (на 1,92%), лізоцимну (на 3,53%) та фагоцитарну активність. Підвищені гематологічні та біохімічні параметри та посилені антибактеріальні властивості сироватки вказують на підвищену метаболічну активність у овець кросу F1 і лежать в основі покращених параметрів виробництва м’яса. Отримані результати свідчать про підвищену пристосованість нового кросу до промислових умов вирощування та місцевого мікроклімату степової зони України, яка зазнає поступової аридизації.
Гематологічні параметри та виробничі характеристики нової породи Романов × Гіссар, адаптовані до європейського степового клімату
Похил Володимир Іванович https://orcid.org/0000-0002-2994-879X Миколайчук Людмила Петрівна https://orcid.org/0000-0001-5331-719X Похил Олена Миколаївна https://orcid.org/0000-0002-7477-6501
Keywords: blood enzymes; ферменти крові; sheep breeding; вівчарство; Romanov × Hissar crossbreed; помісь Романов × Гіссар; meat quality; якість м'яса; haematology; гематологія; animal resistance; стійкість тварин